Analisis Program Edukasi Gizi sebagai Upaya untuk Mencegah Stunting Melalui Pengabdian Kepada Masyarakat - Hani Rarti Syahara Harahap; Inna Muthmainnah Dalimunthe; Muhammad Murdani; Riyanti Riyanti; Siti Izzati Sarah; Tanti Jumaisyaroh Siregar (Lembaga Pengembangan Kinerja Dosen, 2026)
Stunting is a chronic nutritional problem that is still prevalent in the community and has long-term impacts on physical growth, cognitive development, and the quality of human resources. One effort to prevent stunting is through a community service-based nutrition education program. This activity aims to analyze the implementation of a nutrition education program as a stunting prevention effort in Pasar Rawa Village, Gebang District, Langkat Regency, North Sumatra. The method used was a descriptive qualitative approach with a community service approach. The target group included PKK mothers and local mothers with toddlers. The activity was carried out through the delivery of balanced nutrition education materials, an introduction to stunting, and a discussion and question-and-answer session. The results of the activity showed active participant participation and increased awareness of the importance of fulfilling children's nutritional needs. However, some mothers still did not fully understand the concept of stunting, and some toddlers still experienced stunting. Therefore, nutrition education needs to be carried out sustainably and integrated with other health programs.